RESEARCH OF DOUBLE CLOSURES AT GROUND IN NETWORKS 10 KV WITH ISOLATED NEUTRAL - RUBANENKO, OLEKSANDR; RUBANENKO, OLENA; POHRANYCHNYI, BOHDAN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Reliability indicators of power supply systems as a whole are largely determined by the level of reliability of distribution electrical networks with a voltage of 6-35 kV. Emergency in networks with a voltage of 6-35 kV, operating in the mode with an isolated neutral, is often associated with internal overvoltages. Single-phase short-circuits occur in places of defects in the insulation of cable lines and substation equipment due to the aging of the insulation, non-compliance with the manufacturing technology of insulating structures at factories, non-compliance with the requirements of the instructions during the installation and operation of the equipment, as well as due to mechanical damage, which, sometimes at the time of their appearance, lead to only a partial decrease in electrical strength. Overloads lead to defects. Single-phase short-circuits in 10 kV networks that are not eliminated in time can lead to double earth faults. For protection in these networks, such protections as current cut-off, maximum current protection, current cut-off, zero-sequence current protection, current protections with blocking at minimum voltage are used. However, there are cases when there are cases of negative operation of such protections at a 10 kV substation during double earth faults. For example, a phase A short circuit occurred on the first line, which receives power from the buses of the investigated substation, and another short circuit (phase B) occurred on the second line. Instead of tripping the two damaged lines, the input circuit breaker tripped by mistake. This de-energized other (undamaged) lines that are fed from the same bus section as the damaged lines. Under such conditions, further studies of the currents in the lines during double circuits are required. For this, the use of the Matlab application program package is justified. This will significantly reduce the costs of physical modeling and verification of proposed proposals. The paper presents the results of studies of double earth faults in 10 kV networks with an isolated neutral in the "MATLAB" program package.